Sistem Pendukung Keputusan Menentukan Pegawai Teladan Menerapkan Metode Weighted Product (WP) - Muhammad Choirul Fazry; Fauriatun Helmiah; Sudarmin Sudarmin (Forum Kerjasama Pendidikan Tinggi, 2022)
The sub-district government is the government that channels the aspirations of the people from the village/kelurahan to the district and is led by a sub-district head. A camat must be able to regulate and direct the apparatus to carry out quality government services. One of the methods used by the sub-district head to improve quality services is to determine exemplary employees of the sub-district government. This method aims to determine the level of quality of the apparatus in the sub-district office. Apparatus assessment was also carried out by Simpang Empat District to determine the level of quality of the apparatus in this sub-district office. However, the current assessment is still done manually on the assessment sheet and is still subjective, because there are no aspects of the assessment used in the assessment of this exemplary employee. Asahan Regency has a lot of undeveloped potential. From the potential of abundant natural resources, but in human resources there is still very little this is due to the lack of a sense of discipline in the sub-district apparatus in the Asahan area. So it is necessary to have a decision support system in performance appraisal in order to foster morale in the sub-district apparatus. This is what makes researchers want to do research using the Weighted Product (WP) method. The criteria used in this study are attendance, loyalty, attitude and task completion. In this research, we succeeded in applying the Weighted Product method in employee decision making, namely alternative A11 on behalf of Eva Sartika as the number 1 exemplary employee at the Simpang Empat subdistrict office.